Legalidade e legitimidade durate a ditadura militar: o embate entre as estratégias legais de condenação e de resistência no IPM 745, instaurado no Paraná em 1975 - Brunelo, Leandro (2019)
The purpose of this research was to understand how the State appropriated legal mechanisms to legitimize its punitive and legal actions against the political opposition, especially, the militants of the Brazilian Communist Party (PCB) in Paraná in 1975, when they were arrested and indicted by Military-Police Inquiry 745 (IPM 745), which verified the involvement of the Communists in the supposed reorganization of the party in the State. When discussed the IPM and documents produced by the Police Station of the Political and Social Order (DOPS), sources of our research, we try to evoke the voices of the State, as a political institution that controls and formulates laws, and to give visibility to the work of the defense lawyers of the arrested people who, even unprovided from political control, stood face to face with the State. Both the lawyers and the State, were two social and political agents present in a specific field, the legal one, which, it occurred the dispute for monopoly of being able to say or affirm what is right and it was characterized by the clash of the indictment’s and defense’s narratives. Thus, within the juridical field, two ideologically and divergent disparate agents in the scale of power, started a legal and juridical battle and the lawyers, in turn, used the same bureaucratic-legal substratum formulated by the State and legitimator of its actions, to make the limits of the law and the legal field less rigid